1987
DOI: 10.1203/00006450-198703000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Amino Acid Differences in Very Low Birth Weight Infants Fed either Human Milk or Whey-Dominant Cow Milk Formula

Abstract: When VLBW infants are fed a cow milk-based formula, a whey-rather than a casein-dominant formulation is recommended often (1,2). The assumption implicit in this recommendation is that an increased proportion of bovine milk whey in the formula's protein substantially increases the similarity between the formula and human milk (2). Differences in the proteins found in human and bovine wheys, however, weaken this premise. The predominant proteins in human whey are alactalbumin, SIgA, and lactoferrin; those predom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 12 publications
4
17
0
1
Order By: Relevance
“…These results are in accordance with other studies where growth rates, gross metabolic responses, and nitrogen balances are not influenced by the quality of protein used for fortification when similar protein and energy intakes are used [5,9,14,16,21,22].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are in accordance with other studies where growth rates, gross metabolic responses, and nitrogen balances are not influenced by the quality of protein used for fortification when similar protein and energy intakes are used [5,9,14,16,21,22].…”
Section: Discussionsupporting
confidence: 92%
“…The plasma amino acid profiles in LBW infants fed human milk fortified with bovine proteins [4,14] differ significantly from those observed in LBW infants fed exclusively human milk protein [11,13,20,21,22]. The amino acid composition of these bovine fortifiers depends on the amino acid composition of the protein used but it does not fulfill the nutritional needs of preterm infants.…”
Section: Introductionmentioning
confidence: 92%
“…In our study, the amount of free amino acids ranged from 39.65 to 50.40 mg/ 100 mL through the lactation period, and its percentage of total amino acids increased from 2.4 to 4.2% in Taipei and from 1.9 to 3.9% in Kaohsiung. This result was similar to those of other studies (7,15,16). It also seems likely that free amino acids maintain the osmotic pressure of human milk (11) and preferentially contribute to the initial change in plasma free amino acid concentration of the infant because of their early intake (16).…”
Section: Discussionsupporting
confidence: 91%
“…This result was similar to those of other studies (7,15,16). It also seems likely that free amino acids maintain the osmotic pressure of human milk (11) and preferentially contribute to the initial change in plasma free amino acid concentration of the infant because of their early intake (16). The nutritional and physiological significance of these free amino acids re mains to be investigated further.…”
Section: Discussionsupporting
confidence: 90%
“…Free amino acids comprise 8-22% of nonprotein nitrogen and 5-10% of total amino acids in human milk (51)(52)(53). They are an important nitrogen source for the growing infant and are more readily absorbed than protein-derived amino acids (54). In a systematic review of the literature, Zhang et al (55) found that many of the free amino acids in term human milk decrease in concentration during the first 2 mo of lactation, whereas glutamine and glutamate increase.…”
Section: Discussionmentioning
confidence: 99%